Anti-Tumor Activity of Expanded PBMC-Derived NK Cells by Feeder-Free Protocol in Ovarian Cancer - Minhua Chen (MDPI AG, 2021)
Natural killer (NK) cells have shown great therapeutic potential against a wide range of cancers due to their pan-specific target recognition. Numerous reports indicate that NK cell immunotherapy is an effective therapeutic approach for treating hematological malignancies, but shows limited effects against solid tumors. In this study, several models of ovarian cancer (OC) were used to test the anti-cancer effects of NK cells derived from human peripheral blood mononuclear cells and expanded using a feeder cell-free expansion system (eNKs). The results show that eNKs exhibit potent inhibitory activity on tumor growth in different ovarian cancer xenograft mice (i.e., solid tumors, abdominal metastatic tumors, and ascites), importantly, in a dose-dependent manner. Moreover, adoptive transfer of eNKs resulted in significant reduction in ascites formation in OC peritoneal tumor models, and especially in reducing intraperitoneal ascites. We found that eNKs could migrate to the tumor site, retain their activity, and proliferate to maintain high cell counts in cutaneous xenograft mice. In addition, when increased the infusion with a high dose of 12 × 107 cells/mouse, Graft-versus-host disease could be induced by eNK. These data show that eNK cell immunotherapy could be a promising treatment strategy for ovarian cancers, including solid tumors and ascites.